(untitled) (International Journal of Engineering and Computer Science, 2015)
The performance of both temperature and Sunshine dependent models were evaluated for the estimation of global solar radiation over Nigeria using relative sunshine duration, mean monthly minimum and maximum air temperature and extraterrestrial solar radiation (Ro). The monthly global solar radiation was estimated for 10 years (2001-2010). The Angstrom-Prescott (1924), Hargreaves and Sammani (1982) and Garcia (1994) models were used. Sokoto, Enugu, Port Harcourt and Oyo were chosen for the study. New Armstrong –type equations were formulated for each city with new coefficient constants. From the models compared, the improved Angstrom-Type models performed best with a RMSE of 0.00000241, 0.00028, 0.0127, and 0.000935 for Enugu, Oyo, Port Harcourt and Sokoto respectively. This was closely followed by the Hargreaves and Sammani Model and the Angstrom-Prescott model. The Garcia model performed least. Sokoto recorded the highest global solar radiation in Nigeria with the month of April having 21.598MJ/M2/ day, While Oyo has the least with 8.630 MJ/M2/ day during the month of August. Consequently the developed Angstrom-type models can be used with confidence for each of the cities in Nigeria and other locations with similar latitudinal variations